Exploring green human resource management to achieve sustainability in the banking industry of Bangladesh - Hossain, Mohammad Enayet; Mahadi, Nur Farhah; Haron, Razali; Tareq, Mohammad Ali; Mohd Nor, Rizal; Sohel, Rana; Martoza, Md. Golam; Kamrunnaher, Mst. (Springer, 2024)
The bank’s success relies heavily on its dynamic, skilled, capable workforce. Implementing effective human resource management practices ensures a motivated, skilled workforce to achieve the bank’s goals. Green human resource management (GHRM) involves integrating environmentally sustainable practices into all aspects of HR management. This encompasses policies, practices, and systems that encourage employees to use eco-friendly and sustainable resources to benefit individuals, society, the environment, and the business. This research aims to assess the importance of GHRM policies and the impact of sustainable HR initiatives on corporate performance. Social identity theory guided this study, which employed quantitative research using a closed-ended questionnaire to collect data from 210 employees in various banks in Bangladesh. This cross-sectional study experimentally examined hypotheses formulated based on constructive epistemology. The five-point Likert scale questionnaire covered various HRM aspects, such as recruitment, compensation, job security, career development, training, management approach, job design, rewards, motivation, and work environment. The study employed regression analysis, and results showed a positive and significant correlation between HRM practices, including training, fair compensation, career advancement opportunities, job stability, performance evaluation, and the development of trust. This study offers valuable insights for all stakeholders interested in understanding current HRM practices in Bangladesh.